Potential effects of noni (Morinda citrifolia L.) fruits extract against obsessive-compulsive disorder in marble burying and nestlet shredding behavior mice models - Jeyabalan, Srikanth; Bala, Logeshwari; Subramanian, Kavimani; Jabaris, Sugin Lal; Sekar, Mahendran; Wong, Ling Shing; Subramaniyan, Vetriselvan; Chidambaram, Kumarappan; Gan, Siew Hua; Mat Rani, Nur Najihah Izzati; Begum, M. Yasmin; Safi, Sher Zaman; et al. (Frontiers in Pharmacology, 2022)
Obsessive-compulsive disorder (OCD) is a chronic and complex psychiatric disorder that usually includes both obsessions and compulsions. Morinda citrifolia Linn (Noni) is a functional food and it is a well-known plant due to its potential therapeutic effects on human health in many disorders including neurological and neurodegenerative diseases. The purpose of this study was to evaluate the potential effect of M. citrifolia fruits extract (MCFE) against obsessive-compulsive disorder using the marble burying and nestlet shredding behavior mice models. In addition, brain neurotransmitters such as dopamine (DA), serotonin and noradrenaline (NA) were also assessed. Five mice were placed in each of the different groups, and the treatment was given to the animals for a period of 15 days. The marble burying test was evaluated for 30 min on days 1, 7 and 14 while the nestlet shredding test was evaluated for 60 min on days 2, 8 and 15. Treatments with MCFE (100 and 200 mg/kg., p.o.) significantly improved in both behavior tasks when compared to the control group. In addition, standard diazepam (2 mg/kg., i.p.) and fluoxetine (15 mg/kg., p.o.) were also significantly improved in both tasks when compared with the control mice. Further locomotor activity study revealed that MCFE and fluoxetine did not affect the locomotor functions when compared to vehicle treated mice. In contrast, diazepam significantly decreased locomotion when compared to the control group. The significant amelioration of biogenic amines were observed in the MCFE-treated animals with increased serotonin levels. The histopathology of the brain, liver, and kidney tissues after MCFE administration revealed normal morphological structure with no signs of toxicity or abnormalities. All these results together suggest that MCFE can be a potential drug candidate for the treatment of OCD. Future research should focus on the identification and the anti-compulsive activity of the constituents from M. citrifolia.